The Effects of Early Retirement on Youth Unemployment : The Case of Belgium - Pestieau, Pierre (IMF Working Papers; Working Paper ;, 2008)
In this paper, we describe the changes of (early) retirement programs over time and study the link between trends in elderly labor force participation and youth unemployment. From a theoretical point of view, there is no convincing argument that the idea of a lump-of-labor should hold. Our empirical results comfort this finding, and indicate a very weak link, if any, between elderly retirement and activity among the young and the prime-age populations.